Multifunctional agroforestry: A new game-changer for attaining food security and environmental sustainability - A, Keerthika; Parthiban, K T; Sekar, I; Revathy, S; Chavan, S B; Mohamed, M B Noor (Indian Farming, 2023)
Agroforestry has witnessed challenges and changes every decade in the form of technology and marketing interventions. Although agroforestry is promoted for meeting food and nutritional security, it has become the need of the hour to promote multifunctional agroforestry with the main focus on small-scale farmers to provide income throughout the year. Keeping this in mind, a new circular-shaped multifunctional agroforestry was designed at Forest College and Research Institute, Mettupalayam, Tamil Nadu on 0.75 acres incorporating 25 tree species and 08 intercrops mainly to quantify ecosystem services, viz. provisioning services, regulating services, supporting services, and cultural services. In most of the agroforestry systems, the realistic values of supporting and cultural services are sidelined due to the utmost importance given to provisioning services. Therefore, this study has quantified ecosystem services and determined the holistic monetary value of multifunctional agroforestry for three years (2018–2021) as ₹ 374211.42.